High Output External Biliary Drainage Leading to Acute Kidney Injury in a Patient with Malignant Obstructive Jaundice: A Rare Case Report (Nepalese Journal of Radiology, 2023)
Most patients with malignant obstructive jaundice present to the hospital in an advanced unresectable stage. Percutaneous transhepatic biliary drainage (PTBD) and stenting are the established , safe and effective way of palliative treatment aiming prolongation and improving the quality of the life. We report a rare case of high output external biliary drainage leading to AKI and electrolyte imbalance following insertion of PTB drain. Patient was managed with hemodialysis and subsequent self- expandable metallic stent (SEMS) placement. We highlight the importance of awareness of this complication and need of further studies regarding role of biliary interventions, associated complications and management.